Structural, dielectric and gas sensing properties of gadolinium (Gd3+) substituted zinc-manganese nanoferrites. (15th July 2022) - Radu, Ioana; Turcan, Ina; Lukacs, Alexandru V.; Roman, Tiberiu; Bulai, Georgiana-Andreea; Olariu, Marius Andrei; Dumitru, Ioan; Pui, Aurel
Graphical abstract: All 650 ℃ thermal treated ferrite samples exhibit good and reproducible results for the detection of acetone vapors, but the best results were obtained for the sample Zn0.7 Mn0.3 Gd0.1 Fe1.9 O4 which exhibit 53% sensitivity. A direct correlation was observed between the values of relaxation times and samples porosity. Abstract: Gadolinium (Gd 3+ ) substituted zinc manganese ferrite nanoparticles with nominal compositions Zn0.7 Mn0.3 Gdx Fe2-x O4 (where x = 0.000; 0.025; 0.050; 0.075; 0.100) were successfully synthetized using co-precipitation method. The synthetized powders were calcined at 500 °C and furthermore pressed into pellets and thermally treated at 650 °C for a second time to obtain a more compact material. For the 500 ℃ thermal treated samples, X-ray analysis revealed the formation of pure spinel ferrite phase, meanwhile for the 650 ℃ thermal treated samples secondary phases appear which indicate that some of Gd 3+ ions aren't able to remain in the structure of ferrite. The morphology of samples was investigated using scanning electron microscopy (SEM) and the images show agglomerated spherical nanoparticles within 20–30 nm size range. The magnetization curves recorded in ±10 kOe range indicate a superparamagnetic behavior of the synthetized ferrite samples. At low frequencies, the Gd 3+ substituted ferrite samples corresponding to x = 0.050, 0.075 and 0.100 exhibit a resonant behavior of the dielectric losses dependence, while at high frequencies the lowest value was found for the sample with x = 0.025. The introduction of Gd 3+ ions in the ferrite structure leads to a non-monotonous variation of AC electrical conductivity, which decrease from 2.55 x10 −6 S/m to 3 x10 −7 S/m. The ferrite samples have shown a good and reproducible response to the saturated acetone vapors and the highest sensitivity value (53%) was obtained for Zn0.7 Mn0.3 Gd0.025 Fe1.9 O4 ferrite sample. The response and recovery time varies between 36 and 56 s, respectively 80–116 s and both of these are independent of Gd 3+ content.